Academic requirements for Certificate of Completion of Training in surgical training: Consensus recommendations from the Association of Surgeons in Training/National Research Collaborative Consensus Group. (November 2016) - Lee, Mathew J.; Bhangu, A.; Blencowe, Natalie S.; Nepogodiev, D.; Gokani, Vimal J.; Harries, Rhiannon L.; ,; Akinfala, M.; Ali, O.; Allum, W.; Bosanquet, D.C.; Boyce, K.; et al.
Abstract: Background: Surgical trainees are expected to demonstrate academic achievement in order to obtain their certificate of completion of training (CCT). These standards are set by the Joint Committee on Surgical Training (JCST) and specialty advisory committees (SAC). The standards are not equivalent across all surgical specialties and recognise different achievements as evidence. They do not recognise changes in models of research and focus on outcomes rather than process. The Association of Surgeons in Training (ASiT) and National Research Collaborative (NRC) set out to develop progressive, consistent and flexible evidence set for academic requirements at CCT. Methods: A modified-Delphi approach was used. An expert group consisting of representatives from the ASiT and the NRC undertook iterative review of a document proposing changes to requirements. This was circulated amongst wider stakeholders. After ten iterations, an open meeting was held to discuss these proposals. Voting on statements was performed using a 5-point Likert Scale. Each statement was voted on twice, with ≥80% of votes in agreement meaning the statement was approved. The results of this vote were used to propose core and optional academic requirements for CCT. Results: Online discussion concluded after ten rounds. At the consensus meeting, statements were voted on by 25 delegates from across surgical specialties and training-grades. The group strongly favoured acquisition of 'Good Clinical Practice' training and research methodology training as CCT requirements. The group agreed that higher degrees, publications in any author position (including collaborative authorship), recruiting patients to a study or multicentre audit and presentation at a national or international meeting could be used as evidence for the purpose of CCT. The group agreed on two essential 'core' requirements (GCP and methodology training) and two of a menu of four 'additional' requirements (publication with any authorship position, presentation, recruitment of patients to a multicentre study and completion of a higher degree), which should be completed in order to attain CCT. Conclusion: This approach has engaged stakeholders to produce a progressive set of academic requirements for CCT, which are applicable across surgical specialties. Flexibility in requirements whilst retaining a high standard of evidence is desirable.